Isolation and characterization of mayaro virus from a human in Acre, Brazil - Terzian, Ana Carolina Bernardes; Auguste, Albert J.; Vedovello, Danila; Ferreira, Marcelo U.; Silva-Nunes, Monica da; Speranca, Marcia A.; Suzuki, Rodrigo B.; Juncansen, Camila; Araujo Junior, João Pessoa [UNESP]; Weaver, Scott C.; Nogueira, Mauricio Lacerda (Amer Soc Trop Med &hygiene, 2015)
Mayaro virus (MAYV) is widely distributed throughout South America and is the etiologic agent of Mayaro fever, an acute febrile illness often presenting with arthralgic manifestations. The true incidence of MAYV infection is likely grossly underestimated because the symptomatic presentation is very similar to that of dengue fever and other acute febrile tropical diseases. We report the complete genome sequence of a MAYV isolate detected from an Acrelandia patient presenting with fever, chills, and sweating, but with no arthralgia. Results show that this isolate belongs to genotype D and is closely related to Bolivian strains. Our results suggest that the Acre/Mayaro strain is closely related to the progenitor of these Bolivian strains that were isolated between 2002 and 2006.